Addiction treatment in the sunnah - Islam Hassan, Mohammad Yaseen; Isyaku, Hassan; Rohaizan, Baru (2017)
Addiction to alcohol is a general phenomenon that affects communities as a whole, and is one of the intractable problems that governments and institutions are trying address. This study used analytical method based on qualitative data collection and analysis tried to explain the concept of addiction and alcohol, and the role of the Sunnah in the treatment of addiction to alcohol through Islamic laws that prevent Muslims from approaching intoxicants. The most interesting findings of this study is that differences in the names of alcohol do not negate its prohibition; the little of what intoxicates in large quantity is also forbidden. Islam has certainly established rules to prevent people from approaching alcohol. Islam did not begin to resolve the problem of alcohol addiction through punishment, but identified the causes that lead Muslims to alcohol addiction, and then addressed those causes in order to prevent Muslims from being addicted to alcohol.